The Debate on Copyright Term Extension in the US - Widjojo, Adeline Florence; Kaur, Kareena; Kwon, Julia Nahee (Anthology: Inside Intellectual Property Rights, 2023)
Since the beginning of US copyright law, a prevalent interest in increasing the term of protection has predominated in court decisions as the value of intellectual property has strengthened. However, the ever-changing legislature that continually extends copyright term has raised controversy among critics who believe the law has become too broad. The aim of this paper is to examine the progression of copyright extension in the United States as well as to compare the arguments for and against such extension. The paper will also briefly look at the progression of copyright extension in Indonesia.